Metagenomic comparison of the faecal and environmental resistome on Irish commercial pig farms with and without zinc oxide and antimicrobial usage - Daniel Ekhlas; José F. Cobo Díaz; Raúl Cabrera-Rubio; Elena Alexa; Juan M. Ortiz Sanjuán; Edgar Garcia Manzanilla; Fiona Crispie; Paul D. Cotter; Finola C. Leonard; Héctor Argüello; Catherine M. Burgess (Animal Microbiome, 2023)
Abstract Background Antimicrobials and heavy metals such as zinc oxide (ZnO) have been commonly used on Irish commercial pig farms for a 2-week period post-weaning to help prevent infection. In 2022, the prophylactic use of antimicrobials and ZnO was banned within the European Union due to concerns associated with the emergence of antimicrobial resistance (AMR) and contamination of the environment with heavy metals. In this study, faecal and environmental samples were taken from piglets during the weaning period from ten commercial farms, of which five farms used antimicrobial or ZnO prophylaxis (AB-ZnO farms) and five which had not used antimicrobials or ZnO for the previous 3 years (AB-ZnO free farms). A total of 50 samples were compared using a metagenomic approach. Results The results of this study showed some significant differences between AB-ZnO and AB-ZnO free farms and suggested positive selection for AMR under antimicrobial and ZnO treatment. Moreover, strong differences between environmental and faecal samples on farms were observed, suggesting that the microbiome and its associated mobile genetic elements may play a key role in the composition of the resistome. Additionally, the age of piglets affected the resistome composition, potentially associated with changes in the microbiome post-weaning. Conclusions Overall, our study showed few differences in the resistome of the pig and its environment when comparing AB-ZnO farms with AB-ZnO free farms. These results suggest that although 3 years of removal of in-feed antimicrobial and ZnO may allow a reduction of AMR prevalence on AB-ZnO farms, more time, repeated sampling and a greater understanding of factors impacting AMR prevalence will be required to ensure significant and persistent change in on-farm AMR.